The new formula of the Wings for Life World Run charity run during the COVID-19 pandemic - Iwińska, Anna; Pyrgiel, Justyna (Contemporary problems of physical and health culture, 2022)
Wings for Life World Run is a charity run on a global scale. The aim of the project is tocollect funds that are allocated to research related to the invention of effective methods of treatinga broken spinal cord in people who have suffered accidents. The event has been organizedcyclically for eight years. It is attended by amateur athletes from many countries around the world,starting the race on the same day at the designated time (UTC). The article presents the sports resultsobtained by participants of the race in various age categories, which in the years 2020‒2021adopted a new formula due to the limitations related to the COVID-19 pandemic. The changesintroduced by the organizers of the Wings for Life World Run also contributed to the increase in thenumber of participants from 35,397 people in 2014 to 184,236 people in 2021.